Phosphorylated pVEGFR2/KDR receptor expression in uveal melanomas: relation with HIF2α and survival. - Giatromanolaki, A; Sivridis, E; Bechrakis, N; Willerding, G; St Charitoudis, G; Foerster, M; Gatter, K; Harris, A; Koukourakis, M (2012)
Hypoxia and its down-stream activated pathways are commonly involved in tumor progression. Genes involved in angiogenesis and glycolysis, i.e. vascular endothelial growth factor (VEGF) and lactase dehydrogenase A (LDHA), respectively, are transcriptionally controlled by the hypoxia inducible factors 1α and 2α (HIF1α and HIF2α). A series of 60 uveal melanomas were immunohistochemically assessed for the expression of VEGF and the phosphorylated/activated form of VEGF receptor 2 (pVEGFR2/KDR), after binding to VEGF. The expression of HIF1α, HIF2α and LDH5 was also investigated. Uveal melanomas overexpressing HIF2α (but not that of HIF1α) were significantly associated with high VEGF (P = 0.005), pVEGFR2/KDR (P < 0.0001) and LDH5 (P ≤ 0.0001). High LDH5 was linked with tumor necrosis (P = 0.01) and increased tumor size (P = 0.03). High VEGF was linked with phosphorylated pVEGFR2/KDR receptors. In univariate analysis high pVEGFR2/KDR receptor expression was significantly related with poor prognosis (P = 0.02). It is concluded that HIF2α plays an important role in the progression of uveal melanomas possibly by promoting the autocrine loop VEGF-pVEGFR2/KDR, and by enhancing the expression of LDHA gene, conferring thus a growth advantage. As pVEGFR2/KDR expression was significantly related with poor prognosis, inhibitors of this receptor may improve the clinical outcome of patients with pVEGFR2/KDR overexpressing uveal melanomas.